Can radical surgical treatment of the vulva be justified in the absence of a conclusive diagnosis of squamous cell carcinoma on biopsy? A retrospective 10-year cohort study. (May 2020) - Jonker, Lysanne W.; Dasgupta, Shatavisha; Ewing-Graham, Patricia C.; van Doorn, Helena C.
Highlights: Suspicion of vulvar squamous cell carcinoma (VSCC) on pre-operative histopathology is strongly predictive of a final diagnosis of VSCC (p < 0.001). For cases with strong clinical and pathologic suspicion of VSCC, radical treatment helps avoid second surgeries, at the cost of minimal over-treatment. Higher patient age, co-morbidity, low clinical suspicion of carcinoma, or proximity of the tumor to the anus often prompt a surgeon to choose local treatment, despite a suspicion of VSCC on biopsy. Abstract: Objectives: The extent of surgical treatment for vulvar lesions is predominantly guided by the histopathologic diagnosis rendered on the pre-operative biopsy. For premalignant lesions, local excisions are performed, whereas for vulvar squamous cell carcinoma (VSCC), more radical procedures are mandatory. However, even in the absence of a conclusive diagnosis of VSCC on biopsy, the surgeon may opt for a radical excision on grounds of strong clinical suspicion, with a view to avoiding repeat surgeries. We studied a retrospective, 10-year cohort of patients who underwent vulvar excisions, in the absence of a conclusive biopsy diagnosis of VSCC. We aimed to identify the factors predictive of VSCC in these patients, and assess their treatment. Study design: All patients who underwent vulvar excision (2005–2016) at Erasmus MC, without a definitive diagnosis of VSCC on the preoperative biopsy were included. Logistic regression analysis was performed to identify the factors predictive of a final diagnosis of VSCC. Surgical treatment was categorized as definitive, incomplete, or over-treatment, based on histopathology of the excision specimen and previous surgical history. Results: In 57 % (64/113) of all included patients, the final diagnosis was VSCC. Higher patient age (p = 0.03), and suspicion of VSCC on pre-operative biopsy (p < 0.001) were associated with a final diagnosis of VSCC on univariate analysis. Suspicion of VSCC on biopsy was the only significant predictor (p < 0.001) on multivariable analysis. For patients with a suspicion of VSCC on biopsy, radical treatment was more frequently performed (p < 0.001), which resulted in over-treatment in only 1 case. Where the surgeon had performed a limited excision despite a suspicion of VSCC on biopsy, high patient age, co-morbidities, location of the tumor close to the anus, and history of previous vulvar surgeries were factors which influenced the decision. The treatment administered was definitive for 72 %., i.e. additional surgeries were not required; 25 % received incomplete treatment and needed additional surgeries, and 3% received over-treatment. Conclusion: Suspicion of VSCC on biopsy is strongly predictive of a final diagnosis of carcinoma. In our cohort, radical treatment performed on patients with clinical and histopathological suspicion of VSCC resulted in minimal over-treatment, and helped avoid second surgeries.